Is there a conflict between local communities and tourism? Mardin Sample. - Elif Gunduz; Rahmi Erdem (European Regional Science Association (ERSA), 2013)
The inevitable socio-cultural conflict between the tourism industry and local inhabitants in Mardin historic town challenges the tourism development process. The city of Mardin, located on the Tigris side of Southeastern Anatolia has become one of the most attractive cities of Turkey with its natural beauties, cultural heritage and socio-cultural elements and is a candidate city for the World Heritage Sites List with its stone architecture and unique religious and traditional buildings. The level of interrelation between government, residents and foreign visitors is critical in several circumstances, mainly due to the available instruments of territorial planning dealing with tourism policies, the local community benefits specifically from the social and economic point of view, the respect of natural resources and authentic culture of place. Methodologically, comprehending the environmental context in order to connect tangible (physical and material aspects) and intangible (perceptual, tradition or living heritage) factors could contribute to set a suitable and a holistic planning policy to tackle with tourism inconveniencies. This is recommended in alleviating some conflict generators, taking into consideration the investorsâ?? interests, tourists and local community satisfaction.
Keywords: 330; Heritage tourism; Local communities; Economic Socio-cultural Physical and attitudinal changes